A critical geography of disability hate crime. Issue 2 (2nd July 2018) - Hall, Edward
Abstract : Many disabled people experience fear, harassment and occasionally violence in an array of public and private spaces, yet the issue remains unexamined by geographers of disability. To address this research gap, the paper develops a critical geography of disability "hate crime." Extreme, yet rare, violent acts against disabled people constitute the popular and policy imagination of disability hate crime. While clearly important, these cases characterise disability hate crime as individually‐targeted placeless acts of extreme abjection against disabled people. At the same time, they arguably draw attention away from everyday "low‐level" harassment, name‐calling, fear, and neglect experienced by many in mainstream spaces and the impact on senses of social inclusion and belonging. Citing "race"‐related hate crime studies, which have recognised the role of social and physical environments in shaping incidence, the paper seeks to shift research and, in turn, policy on disability hate crime towards the local and micro‐scale spaces and moments within which incidents occur, and the social relations that constitute these acts, in the context of an exclusionary disablist society. The paper is organised in two parts: first, evidence of harassment and violence experienced by disabled people (UK‐focused) is examined and the emergence of disability "hate crime" critiqued; second, a critical geography of disability hate crime is developed, applying insights from hate crime studies and relational geographies of disability. The paper concludes by setting out an agenda for Geography's potential contribution to disability and wider hate crime research.